Mechanical phase inversion of Pickering emulsions via metastable wetting of rough colloids. Issue 39 (18th September 2019) - Zanini, Michele; Cingolani, Alberto; Hsu, Chiao-Peng; Fernández-Rodríguez, Miguel Ángel; Soligno, Giuseppe; Beltzung, Anna; Caimi, Stefano; Mitrano, Denise; Storti, Giuseppe; Isa, Lucio
Abstract : We exploit the surface-roughness-induced wetting hysteresis of individual colloids to achieve Pickering emulsions undergoing phase inversion upon mechanical energy inputs. Abstract : The possibility to invert emulsions from oil-in-water to water-in-oil (or vice versa ) in a closed system, i.e. without any formulation change, remains an open fundamental challenge with many opportunities for industrial applications. Here, we propose a mechanism that exploits particle surface roughness to induce metastable wetting and obtain mechanically-responsive Pickering emulsions. We postulate that the phase inversion is driven by an in situ switch of the particle wettability from metastable positions at the interface following the input of controlled mechanical energy. Oil-in-water emulsions can be prepared at low energy using mildly hydrophobic rough colloids, which are dispersed in water and weakly pinned at the interface, and switched to water-in-oil emulsions by a second emulsification at higher energy, which triggers the relaxation of the particle contact angle. The same principle is demonstrated for the complementary emulsions using mildly hydrophilic colloids initially dispersed in oil. Our experiments and simulations support that the delicate interplay between particle surface design during synthesis and the energy of the emulsification process can encode a kinetic pathway for the phase inversion. Both organic and inorganic nanoparticles can be used, allowing for the future implementation of our strategy in a broad range of smart industrial formulations.